Autoantibodies Response to MDM2 and p53 in the Immunodiagnosis of Esophageal Squamous Cell Carcinoma. (November 2014) - Chai, Y.; Peng, B.; Dai, L.; Qian, W.; Zhang, Y.; Zhang, J.‐Y.
Abstract The human homologue of the mouse double minute 2 (MDM2) is known to be overexpressed in a variety of human malignancies. As one of E3 ubiquitin–protein ligases, MDM2 interacts with the tumour suppressor p53 by mediating ubiquitination and degradation of p53. Since abnormally expressed proteins can induce autoimmune response, to further examine whether sera from patients with esophageal squamous cell carcinoma (ESCC) exhibited immunoreactivity against MDM2 and p53, autoantibody responses to MDM2 and p53 were evaluated by enzyme‐linked immunosorbent assay (ELISA) in sera from patients with ESCC and normal individuals. Positive results were also confirmed by Western blotting and indirect immunofluorescence assay. The results demonstrated that the positive rate of autoantibody against p53 and MDM2 in ESCC sera was 22.9% (36/157) and 14.0% (22/157), whereas this rate was 0% (0/85) and 1.2% (1/85), respectively, in normal individuals. Some of the sera with antibodies specific for MDM2 also contained antibodies against p53. And there was an increase of positive antibody reactions reaching a frequency of 35% (55/157) combination with MDM2 and p53. This was significantly higher than the frequency of antibodies in normal individuals (P < 0.01). Our preliminary results suggest that autoantibodies against MDM2 and p53 may be useful serum biomarkers in the immunodiagnosis of ESCC.